Fruit quality evaluation of different mulberry varieties - Tian, Jie; Wen, Haichao; Liu, Bingxiang; Tian, Xinyuan; Wu, Yibo; Yang, Jingyan; Zhang, Bingying; Li, Hongjiao (Frontiers in Plant Science, 2025)
The quality of fruits has long been a key focus for breeders,and the development of scientifically sound and reasonable methods for evaluating fruit quality is of great significance in selecting superior cultivars.The mulberry tree contains rich nutritional components and various bioactive compounds.These include properties such as immune enhancement,lipid-lowering effects, and anti-tumor activities.Therefore,to select mulberry varieties with superior quality and adapt to the diversification trends in mulberry development,this study uses 21 mulberry varieties to analyze and compare differences in fruit appearance quality,nutritional quality, functional components,and antioxidant capacity.PCA was employed to identify core evaluation indices,and the Entropy Weight Method was used to assign weights based on these core quality indices.Subsequently,GRA was used for a comprehensive evaluation of the fruit quality of the 21 mulberry varieties.The results indicate that, in terms of appearance quality,varieties such as 'Ri Ben Guo Sang', 'Hong Guo 1', 'Lv Shen Zi', 'He Lan Sang', and 'Ju Shen' stand out overall. In terms of nutritional quality,'Tang 10' has relatively higher levels of free amino acids and soluble proteins.Overall,varieties such as 'Jiang Mi Guo Sang', 'Bai Shen 2', 'Ji Gui Hua', 'Xiao Bai E', 'Da Bai E', and 'Da Yi Bai' stand out in terms of comprehensive quality.Regarding functional components,the four varieties-'Lv Shen Zi', 'Hei Zhen Zhu', 'He Lan Sang', and 'Da 10'-are prominent across all indicators.In terms of antioxidant capacity, 'Jiang Mi Guo Sang', 'Hong Guo 1', 'Xiao Bai E', 'Da Bai E', and 'Da Yi Bai' rank relatively high, which largely overlaps with the varieties selected for their nutritional quality.Regarding fruit enzyme activity, 'Ri Ben Guo Sang', 'Hong Guo 1', 'Lv Shen Zi 1', 'Lv Shen Zi 2', 'He Lan Sang', and 'Da 10' show high enzyme activities.Finally, the index was extracted by PCA and weighted by entropy weight method.GRA was used to calculate the final correlation degree, which ranged from 0.406 to 0.817.This study suggests that varieties such as 'Da 10', 'Feng Guo Sang', 'He Lan Sang', 'Lv Shen Zi', and 'Ri Ben Guo Sang' exhibit superior overall fruit quality and rich nutritional value,providing a theoretical basis for the selection,development, and utilization of future mulberry fruit varieties.